Physicochemical properties of duck (Khaki Campbell) skin gelatin pre-treated with acetic acid and citric acid - Alya Afza Abdul Kadir; Nurul Huda; Zarinah Zakaria; Che Abdullah Abu Bakar; Norshazila Shahidan (2020)
Gelatin is the main derivative of a collagen obtained by partial hydrolysis of collagenous material and has unique properties which are the ability to form thermo-reversible gels and emulsion (Rasli and Sarbon, 2015). These properties contribute to a wide range of application in many industrial fields such as food industry, pharmaceutical, cosmetic and photographic industry due to its functionality. According to Sompie et al. (2015) the higher quality of gelatin depends on its physical and chemical properties, rheological properties and manufacturing method. The awareness of the halal product is not only concerned for the muslim consumers but also non-muslim consumers. The non-muslim consumers preference about the halal issue is related to some factors such as hygiene, quality and safety of the product provided from a halal product. There are many issues related to the halal and one of them is gelatin. In addition, the halal issue is arisen when the gelatin used comes from prohibited sources such as porcine, the animal that is not slaughtered according to shariah law such as bovine (Fathin et al., 2018).